Writing Difficulties Faced by Politeknik Kuching Sarawak Commerce Diploma Students in Doing their Assignments - Gee Whai, M.K.; Wei, W. T.; Man, C.K. (The Asian Journal of English Language & Pedagogy, 2013)
Writing is one of the four main skills in learning and it is important especially in the academic context where students have to write all sorts of texts such as assignments, essays and reports. Often, second language students find that it is difficult to express their thoughts in writing, especially when they have to write in English. Therefore, the purpose of this study was to investigate the writing difficulties faced by the Politeknik Kuching Sarawak Diploma students when writing their assignments. The respondents of this study comprised 132 students who had enrolled in the A4004 English for Commercial Purposes course. Questionnaires were used to collect data from the respondents. The information gathered from the questionnaires was then analyzed using descriptive statistics (frequency count and percentage). The findings showed that the students faced major difficulties in completing writing tasks that required creativity and/or critical thinking. They also faced problems in proofreading and in writing grammatical sentences. It was also found that students often thought in their first language and translated their thoughts into English when writing assignments. Other difficulties encountered by the students included not being able to decide on the correct tenses, and differentiating between British English and American English. Some also encountered difficulties in finding suitable words to say what they meant.